ANALISIS PENDAPATAN PETANI PENGGARAP PADA USAHATANI PADI SAWAH DI DESA KALEKE KECAMATAN DOLO BARAT KABUPATEN SIGI - Rustam Abd Rauf, Alimuddin Laapo, Ardianto Mokodongan, (AGROTEKBIS, 2016)
This research aims to 1). Know the characteristics of the sharecroppers on the rice farming in the village of Kaleke Sub District West Dolo Sigi Regency, and 2). Know the earned income sharecroppers on the rice farming in the village of Kaleke Sub District West Dolo Sigi Regency. Sampling taken in this study was by using saturated sampling methods (census), the number of samples taken in this research is 42 people from a population of 42 sharecroppers on the rice farming. The analysis used were descriptive analysis and analysis of revenue. The results of the analysis showed that in the associated with the characteristics of sharecroppers on the rice farming in the village of Kaleke Sub District West Dolo Sigi Regency, average asÂ was productive asÂ educational level of respondents on average in high school, and experience farming respondents mostly ranging between 10-20 years. System of the sharing outcome that is in the village of Kaleke is revenue sharing system where sharecroppers have the right of 70% and land owners the right of 30% of income. But the whole operational costs during the production process are covered by sharecroppers. The average income of the sharecroppers the rice farming in the village of Kaleke Sub District West Dolo Sigi Regency with 0.67 Ha land area amounting of Rp. 7.583.590,87 for a growing season and conversion of land area 1 Ha Rp. 11.375.386,31 for a growing season.